2015
DOI: 10.14214/sf.1239
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of portable tools in assessing the bearing capacity of forest roads

Abstract: Applicability of portable tools in assessing the bearing capacity of forest roadsKaakkurivaara T., Vuorimies N., Kolisoja P., Uusitalo J. (2015). Applicability of portable tools in assessing the bearing capacity of forest roads. Silva Fennica vol. 49 no. 2 article id 1239. 26 p. Highlights• The dynamic cone penetrometer (DCP) and light falling weight deflectometer (LFWD) are useful tools for measuring bearing capacity.• The measurement results are not same as with the falling weight deflectometer (FWD), but co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…In accordance with previous studies (Venäläinen et al, 2001a, b;Kellomäki et al, 2010), our results suggest that climate warming will lead to shorter soil frost periods, reducing wintertime ground-bearing capacity. Also a reduction in snow cover contributes to decreasing bearing capacity (Räisänen and Eklund, 2012).…”
Section: Evaluations Of Main Results and Their Implications On Forestrysupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with previous studies (Venäläinen et al, 2001a, b;Kellomäki et al, 2010), our results suggest that climate warming will lead to shorter soil frost periods, reducing wintertime ground-bearing capacity. Also a reduction in snow cover contributes to decreasing bearing capacity (Räisänen and Eklund, 2012).…”
Section: Evaluations Of Main Results and Their Implications On Forestrysupporting
confidence: 93%
“…Previous studies have indicated that the climate warming leads, unsurprisingly, to reduced soil frost depth and shorter soil frost periods (e.g. Venäläinen et al, 2001a, b;Kellomäki et al, 2010;Gregow et al, 2011;Jungqvist et al, 2014). This may shorten the winter harvesting season with good ground-bearing capacity, particularly on drained peatlands, having thus mainly negative impacts on the forestry sector.…”
Section: Introductionmentioning
confidence: 99%
“…The trafficability of forest roads can be estimated by assessing their bearing capacity by means of penetrometers or a falling weight device (Kaakkurivaara et al 2015). Some of the most frequently used devices are the light falling weight deflectometer (LFWD), dynamic cone penetrometer (DCP) and conventional falling weight deflectometer (FWD).…”
Section: Forest Road Inventoriesmentioning
confidence: 99%
“…The bearing capacity of forest sites is clearly higher during frozen than unfrozen conditions. In addition, small forest truck roads having light foundations do not bear heavy timber trucks in wet road sections unless the soil is frozen (Kaakkurivaara et al, 2015). Operations in poorly bearing conditions increase rut formation on forest floor and tend to cause damage to tree roots and stems (Sirén et al, 2013;Pohjankukka et al, 2016).…”
Section: Less Soil Frostmentioning
confidence: 99%